Violence against women and the relationship with depression: a study in a primary health care unit in the city of Cascavel (Research, Society and Development, 2023)
Violence against women causes different repercussions on the victims' physical and mental health and quality of life, and creates progressive challenges for health professionals. It is estimated that one of the most frequent psychological symptoms is related to depressive disorders. Given the above, the present study aimed to quantify and relate domestic violence and levels of depression among users of the Primary Care Network of the Unified Health System in the city of Cascavel - Pr. 108 women were interviewed, using the Abuse Assessment Screen (AAS), translated and adapted, and the Beck Depression Inventory (BDI). To carry out a statistical comparison between the described variables, the Chi Square, Fisher and Haldane correction tests were used. Of the research participants, 61 (56.5%) stated that they had already suffered some type of physical or psychological violence from their partner or someone important. Among the victims, 32 (52.5%) had symptoms of depression (p=0.06). The results reinforce the importance of carrying out further studies on the subject, with greater screening among the population, in addition to targeted qualification of the multidisciplinary teams of health services.